2015
DOI: 10.1111/pbi.12447
|View full text |Cite
|
Sign up to set email alerts
|

An RNA‐Seq‐based reference transcriptome for Citrus

Abstract: Summary Previous RNA‐Seq studies in citrus have been focused on physiological processes relevant to fruit quality and productivity of the major species, especially sweet orange. Less attention has been paid to vegetative or reproductive tissues, while most Citrus species have never been analysed. In this work, we characterized the transcriptome of vegetative and reproductive tissues from 12 Citrus species from all main phylogenetic groups. Our aims were to acquire a complete view of the citrus transcriptome la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 91 publications
2
18
0
Order By: Relevance
“…The resulting clean reads were then aligned to the Citrus sinensis reference genome ( Xu et al , 2013 ) ( http://citrus.hzau.edu.cn/orange ) using the software SOAPaligner/SOAP2 ( Li et al , 2009 ) allowing two bp mismatches per read. We note that this approach excluded genes that are not present in the C. sinensis genome, or which are divergent between C. sinensis and P. trifoliata / C. trifoliata ; nevertheless, approximately 74% of the RNA-seq reads could be mapped, which was similar to previous RNA-seq analyses for Poncirus ( Terol et al , 2016 ; Chen et al , 2017 ; Supplementary Table S1 ). Gene expression levels were calculated using the RPKM (reads per kb per million reads) method as follows: RPKM = 10 6 × [(Number of reads uniquely aligned to gene A)/(Total number of reads that uniquely aligned to all genes)] × [(Number of bases of gene A)/10 3 ] ( Mortazavi et al , 2008 ).…”
Section: Methodssupporting
confidence: 72%
“…The resulting clean reads were then aligned to the Citrus sinensis reference genome ( Xu et al , 2013 ) ( http://citrus.hzau.edu.cn/orange ) using the software SOAPaligner/SOAP2 ( Li et al , 2009 ) allowing two bp mismatches per read. We note that this approach excluded genes that are not present in the C. sinensis genome, or which are divergent between C. sinensis and P. trifoliata / C. trifoliata ; nevertheless, approximately 74% of the RNA-seq reads could be mapped, which was similar to previous RNA-seq analyses for Poncirus ( Terol et al , 2016 ; Chen et al , 2017 ; Supplementary Table S1 ). Gene expression levels were calculated using the RPKM (reads per kb per million reads) method as follows: RPKM = 10 6 × [(Number of reads uniquely aligned to gene A)/(Total number of reads that uniquely aligned to all genes)] × [(Number of bases of gene A)/10 3 ] ( Mortazavi et al , 2008 ).…”
Section: Methodssupporting
confidence: 72%
“…In the current study only CLC Genomics Workbench was used for sequence assembly since many previous studies have been demonstrated that CLC genomics workbench is most efficient tools based on different assessment parameters specifically N50 length and average contig length (Misner et al, 2013). Transcritome assembly for various organisms including Cleome spinosa and Cleome gynandra (Brautigam et al, 2011), Amycalatopsis orientalis (Jeong et al, 2013), Dodonaea viscosa (Christmas et al, 2015) and 12 Citrus Species (Terol et al, 2016) have already been done using same approach.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have pointed out a higher metabolic activity in the leaves of A. marmelos, which is because of the presence of phytochemicals such as alkaloids, flavonoids, and phenols [47,48]. We have identified a number of GO terms in the leaves of A. marmelos; this information could lead to the identification of important pathways of metabolic compounds in A. marmelos [49].…”
Section: Go Annotationmentioning
confidence: 76%